A single acute alcohol intoxication before fracture insult causes long-term elevated systemic RANKL and OPG levels in young adult mice - Katrin Bundkirchen; Weikang Ye; Tianqi Zhang; Friederike Weidemann; Stefan Lienenklaus; Bastian Welke; Helen Rinderknecht; Borna Relja; Claudia Neunaber (Scientific Reports)
Abstract Binge drinking is the most common form of alcohol abuse and 25–40% of orthopedic trauma patients are intoxicated upon admission. While alcohol consumption prolongs the healing time of bone fractures, the underlying mechanisms by which alcohol leads to this fracture healing disorder remain unclear. 240 young adult and aged male C57BL/6J mice were examined. Half of the animals were acutely alcoholized two hours before surgery. The isolated fracture (Fx) group underwent an externally stabilized osteotomy and another group (THFx) an additional trauma hemorrhage (TH). The Sham group only received catheterization and fixation. Histological, radiological, biomechanical and systemic examinations were performed. Data were analyzed using two-way ANOVA and p ≤ 0.05 was considered significant. After 3 weeks, acute alcoholization led to increased receptor activator of NF-κB ligand (RANKL), osteoprotegerin (OPG) and RANKL/OPG ratio after fracture in young adult mice. In aged animals, this effect of alcohol was not present as values were already increased in the sober ones. More osteoblasts and macrophages were found in alcoholized young Fx animals. In conclusion, one-time binge drinking before trauma causes a long-term change in the RANKL/OPG ratio towards more RANKL in young adult mice.